Isorhamnetin exerts anti-proliferative effect on cancer-associated fibroblasts by inducing cell cycle arrest - Ganbold, Munkhzul; Louphrasitthiphol, Pakavarin; Miyamoto, Takafumi; Miyazaki, Yoshihiro; Oda, Tatsuya; Tominaga, Kenichi; Isoda, Hiroko (Biomedicine & pharmacotherapy, 2025)
Isorhamnetin (ISO), a dietary flavonoid, has been shown to possess antioxidant, anti-cancer, and anti-inflammatory properties. Cancer-associated fibroblasts (CAFs), found in the tumor microenvironment of several types of cancer including pancreatic ductal adenocarcinoma (PDAC) impact the tumor growth and development of chemoresistance. Thus, modulating CAFs is an attractive mean to increase the efficacy of therapies targeting cancer cells. In this study, the anti-proliferative effect of ISO and the underlying transcriptomic profile of ISO-treated PDAC-derived CAFs were investigated. ISO treatment showed a time- and concentration-dependent decrease in cell viability with a slight increase in apoptotic cells. Microarray and cell cycle analyses revealed ISO induced downregulation of pathways in cell cycle and DNA replication; and G2/M checkpoint. Cell cycle analysis showed cells in the G2/M phase were increased. In response to the treatment, hallmark for p53 pathway genes, known to regulate cell cycle checkpoints, were highly upregulated. Moreover, ISO-treated cells had an increased area of the mitochondrial network, but lower mitochondrial membrane potential accompanied by a decrease of ATP production, measured by oxygen consumption rate. Inflammatory gene expression of IL1A1, IL6, CXCL1, and LIF were significantly inhibited in ISO-treated CAFs. Taken together, our results demonstrated that the cytostatic effect of ISO on human CAFs was mediated by inducing cell cycle arrest at G2/M phase associated with activation of p21, impaired mitochondrial homeostasis, and inhibition of inflammatory mediators gene expression, warranting further investigation for its use in combinatorial therapy that target both the cancer and the tumor microenvironment as a whole. [Display omitted] •Isorhamnetin (ISO) decreased cell viability of pancreatic cancer-associated fibroblasts (CAFs).•Microarray analysis revealed that ISO inhibited cell proliferation by inducing G2/M cell cycle arrest in CAFs.•Mitochondrial function was dysregulated by ISO treatment.•Inflammatory marker gene expressions were significantly inhibited by ISO treatment.